Energy-led domestic retrofit: impact of the intervention sequence. Issue 1 (2nd January 2016) - Simpson, Sophie; Banfill, Phil; Haines, Victoria; Mallaband, Becky; Mitchell, Val
Abstract : Interviews conducted with householders reveal that energy efficiency is often a lesser motivation than other factors for undertaking home improvement work. Homeowners' approach to refurbishment is typically staged over several years, not as a whole-house retrofit. As the operational performance of an individual emission-reducing technology typically depends on what other measures are already in place, the retrofit intervention sequence can potentially affect the overall performance of the dwelling. The impact of the intervention sequence on a semi-detached 1930s' house is investigated with dynamic thermal modelling, using five sequences based on different homeowner personas developed from qualitative interviews. The results show that whilst a whole-house retrofit would reduce cumulative CO2 emissions over 25 years by 54%, the sequences actually implemented by the individual households result in significantly smaller reductions of between 42% and 24%. This variation in operational performance due to the intervention sequence means that there is a variable return on the investment for a particular technology and, significantly, that different sequences will yield different cumulative emission reductions. This has significant consequences for policies providing financial incentives for energy-led retrofit, particularly to include the intervention sequence and timing.